Rck of Salmonella Typhimurium Delays the Host Cell Cycle to Facilitate Bacterial Invasion - Mambu, Julien; Barilleau, Emilie; Fragnet-Trapp, Laetitia; Le Vern, Yves; Olivier, Michel; Sadrin, Guillaume; Grépinet, Olivier; Taieb, Frédéric; Velge, Philippe; Wiedemann, Agnès (Frontiers in Cellular and Infection Microbiology, 2020)
Salmonella Typhimurium expresses the outer membrane protein Rck able to interact with the epidermal growth factor receptor (EGFR) of the plasma membrane of the targeted host cells. This interaction activates signaling pathways, leading to the internalization of Salmonella. Since EGFR plays a key role in cell proliferation, we aimed to determine the impact of Rck mediated infection on the host cell cycle. By analyzing the DNA content of uninfected and infected cells using flow cytometry, we showed that the Rck-mediated infection induced a delay in the S-phase (DNA replication phase) of the host cell cycle, independently of bacterial internalization. We also established that this Rck-dependent delay in cell cycle progression was accompanied by an increased level of host DNA double strand breaks and activation of the DNA damage response. Finally, we demonstrated that the S-phase environment facilitated Rck-mediated bacterial internalization. Consequently, our results suggest that Rck can be considered as a cyclomodulin with a genotoxic activity.